Qualificando a adesão Ã democracia: quão democráticos são os democratas brasileiros? - Fuks, Mario; Casalecchi, Gabriel Avila; Gonçalves, Guilherme Quaresma; David, Flávia Felizardo (Revista Brasileira de Ciência Política, 2016)
Resumo O presente artigo busca qualificar a adesão Ã  democracia no Brasil. Ele parte da ideia de que a adesão Ã  democracia é mais bem entendida de um ponto de vista multidimensional. Os indivíduos podem aderir a diferentes princípios subjacentes Ã  democracia, em vez de optarem pela simples adesão ou não a ela. Nosso enfoque são os democratas: queremos saber quão democráticos são os democratas brasileiros. Utilizamos aqui o banco de dados Barômetro das Américas de 2006 a 2012. Os resultados mostram que existem diferentes níveis de adesão Ã  democracia, conforme o princípio democrático em questão. Os brasileiros aderem com maior intensidade Ã  dimensão participativa, em detrimento da procedimental e da representativa. Mostramos, no entanto, que esses princípios podem caminhar de forma mais ou menos independente. Palavras chave: adesão Ã  democracia, apoio político, legitimidade política, atitudes políticas, consolidação da democracia. Abstract This article aims to qualify the support for democracy in Brazil. He starts from the idea that support for democracy is better understood from a multidimensional point of view. That is, individuals may adhere to different principles underlying democracy, rather than simple adherence to the political regime or not. Our focus is on the Democrats. Based on the multidimensional view, we want to know how democratic are the Brazilian Democratic. To meet this goal, we use the database of the Americas Barometer data from 2006 to 2012. The findings show that there are different levels of adherence to democracy, as the democratic principle in question. Brazilians adhere more strongly participatory dimension, rather than procedural and representative. We have shown, however, that these principles are not strongly connected to each other, ie they can move relatively independently. Keywords: support for democracy, political support, political legitimacy, political attitudes, consolidation of democracy